2021
DOI: 10.1037/xlm0001042
|View full text |Cite
|
Sign up to set email alerts
|

Is this going to be on the test? Test expectancy moderates the disfluency effect with sans forgetica.

Abstract: The preregistered analysis plan for Experiment 1 can be found here: https://osf.io/wgp9d.The preregistered analysis plan for Experiment 2 can be found here: https://osf.io/3xak9. The preregistered plan for Experiment 3 can be found here: https://osf.io/hjnk5. All raw and summary data, materials, and R scripts for preprocessing, analysis, and plotting for Experiments 1, 2, and 3 can be found at https://osf.io/cqp6s/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The marginally significant difference in the first block and no reliable difference in the remaining two blocks could be interpreted as due to the moderating effect of test expectancy found in Geller and Peterson [24]. In that study, the high test expectancy was set by the instructions: "your memory will be tested for words in different typefaces" while low test expectancy was set by instructions: "you will be reading words in different typefaces".…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The marginally significant difference in the first block and no reliable difference in the remaining two blocks could be interpreted as due to the moderating effect of test expectancy found in Geller and Peterson [24]. In that study, the high test expectancy was set by the instructions: "your memory will be tested for words in different typefaces" while low test expectancy was set by instructions: "you will be reading words in different typefaces".…”
Section: Resultsmentioning
confidence: 86%
“…When performance across the three blocks was averaged, there was a significant difference in hit rate but when blocks were analyzed individually, only the first block had a difference with marginal significance. One possible explanation for this is that there was less test expectancy in the first block than the remaining two blocks and test expectancy has been identified as a moderator of the SF effect on studied words [24]. Experiment 2 had some surprising results.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…And Eskenazi and Nix (2021) found that Sans Forgetica improved memory for the spelling of obscure words (e.g., abrogate, otiose), but only for high-skill spellers. In terms of its metacognitive effects, Sans Forgetica was judged as more difficult to read than Arial font in Taylor et al (2020), and it yielded lower judgments of learning in Geller and Peterson (in press; but not in Geller et al, 2020 or Taylor et al, 2020).…”
Section: Effects Of Reading Aloudmentioning
confidence: 92%
“…More recently, Sans Forgetica has been found to be helpful under some conditions. Geller and Peterson, in press) found improved recognition, but only when participants were not expecting a memory test. And Eskenazi and Nix (2021) found that Sans Forgetica improved memory for the spelling of obscure words (e.g., abrogate, otiose), but only for high-skill spellers.…”
Section: Effects Of Reading Aloudmentioning
confidence: 98%